Low-Temperature Microwave Pyrolysis Of Sewage Sludge - Wahi, Rafeah; Idris, Azni; Mohd Salleh, Mohamad Amran; Khalid, Kaida (Federation of Engineering Institutions of Islamic Countries, 2006)
Microwave pyrolysis is proposed as one of several optional technologies for disposing and recycling sewage waste in Malaysia. In this study, sewage sludge was dried and pyrolyzed at low temperature (maximum 650ºC) in a single process at laboratory scale. Sewage sludge was placed in a quartz reactor, which was placed in a microwave cavity oven. The modified household microwave oven used has a frequency of 2.45 GHz and input power of 700 W. Graphite was used as microwave absorber in order to facilitate the sewage sludge to reach temperature required for pyrolysis process to take place. The carbonaceous residue (char) and pyrolytic oil produced were analyzed for the proximate and ultimate composition and the gross calorific value. It is found that in this study, the overall heating rate was 118 ºC/min with heating time of 5 minutes. Microwave pyrolysis of sewage sludge at 650°C gives rise to formation of about 28% char, 6% pyrolytic oil and 68% noncondensable gases (dry basis).The gross calorific value of the pyrolytic oil was 28852 kJ/kg, which is higher than that of lignite and sub-bituminous coal thereby reflecting the potential of this fraction as fuel material.